Management of disc displacement with reduction with intermittent locking, myofascial pain, and TMD-Related headache : A Case Report - Andita Nurseptiani Lukman; Rasmi Rikmasari (Indonesia Prosthodontic Association, 2026)
Temporomandibular disorders (TMD) refer to a group of problems involving the temporomandibular joint (TMJ) and the masticatory muscles. The most common intra-articular diagnosis is disc displacement with reduction; however, cases with intermittent locking are relatively rare and can be characterized by fluctuating symptoms. This case report describes the conservative management of disc displacement with reduction with intermittent locking accompanied by myofascial pain with referral and headache attributed to TMD in a 23-year-old male patient. The patient came in with a one year history of left TMJ clicking, recurrent locking episodes, jaw pain, and sharp temporal headache. A clinical examination showed corrected deviation while opening the mouth, limited pain-free mouth opening, joint sounds, myofascial pain with referral, and headache reproduction when the muscles were palpated. The final diagnosis was disc displacement with reduction with intermittent locking complicated with myofascial pain with referral and headache attributed to TMD. Management was a combination of mandibular stabilization splint therapy, muscle conditioning exercises, and physical self regulation. Subsequent visits showed improvement in muscle pain, headaches, joint sounds and locking episodes. Conservative management with stabilization splint therapy supported by behavioral and muscle conditioning interventions can lead to successful symptom relief and functional improvement. Keywords: Temporomandibular disorders, disc displacement with reduction, myofascial pain, headache attributed to TMD, stabilization splint